1983
DOI: 10.1007/bf01990095
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation in golden hamsters (Mesocricetus auratus, W.) exposed to 5% CO2

Abstract: Chronic exposure of golden hamsters to a gas mixture containing 5% CO2, 21% O2, and 74% N2 favors entry into hibernation. In the hibernating golden hamster, however, chronic CO2 exposure facilitates arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies suggested that hypercapnia and hypoxia may induce or facilitate entry into torpor by suppressing metabolism (Studier and Baca, 1968;Williams and Rausch, 1973;Schäfer and Wünnenberg, 1976;Kuhnen et al, 1983). But there are also contrary observations described in the literature.…”
Section: Preparation For Entrance Into Torpormentioning
confidence: 96%
“…Several studies suggested that hypercapnia and hypoxia may induce or facilitate entry into torpor by suppressing metabolism (Studier and Baca, 1968;Williams and Rausch, 1973;Schäfer and Wünnenberg, 1976;Kuhnen et al, 1983). But there are also contrary observations described in the literature.…”
Section: Preparation For Entrance Into Torpormentioning
confidence: 96%
“…For instance, respiratory acidosis in an euthermic hamster induced by breathing 10% CO2 results in depression of hypothalamic neuronal activity involved in thermoregulation (Wiinnenberg and Baltruschat 1982). This could facilitate the lowering of Tset and entry into hibernation as has been demonstrated in hamsters under 5% CO2 , 21 % O 2 , and 74% N 2 (Kuhnen et al 1983). Further, glycolysis is severely depressed by acidosis due to the inhibition of phosphofructokinase by low pH, which dissociates the catalytically -120 Torr Fig.…”
Section: Respiratory Functionsmentioning
confidence: 89%